6 The impact of chronic ankle instability: a systematic review. (12th October 2015) - Hiller, CE; Nightingale, EJ; Raymond, J; Delahunt, E; Thomas, AC; Terada, M; Gribble, PA
Abstract : Background: The influence of CAI on general health and quality of life is largely unknown. In particular any associations between CAI and cardio-metabolic disease risk factors, chronic musculoskeletal co-morbidities, or reduced quality of life have not been substantiated. Objective: To examine the association between CAI and detrimental long-term health effects or decreased quality of life. Design: Systematic review with meta-analysis. Setting: Not applicable. Participants: Studies where people with any symptoms of CAI following an ankle sprain were compared to a non-injured control group. Search strategy: AMED, CINHAL, EMBASE, MEDLINE and SPORTDiscus were searched from inception to July 2015 with no language or geographic restrictions. Two independent reviewers were involved at all stages of title, abstract and full text review, and data extraction. Main outcome measurements: The primary outcomes were any that investigated impact in the following areas: cardio-metabolic disease, arthritis and musculoskeletal disorders, or quality of life. Results: The initial search resulted in 13, 078 titles after removal of duplicates. Data extracted from 22 full texts revealed that participants with CAI have higher BMI and lower exercise levels. One study demonstrated degenerative changes in tibial and talar cartilage in young adults with CAI. Quality of life was the most studied area with the FADI/FAAM being the most popular outcome measures. A meta-analysis of FADI/FAAM measures demonstrated decreased self-reported function and increased disability in people with CAI for both the activities of daily living and sports subscales. Conclusions: There are health and quality of life effects for people with CAI. The evidence for increased risk of cardio-metabolic disease and ankle arthritis is sparse, but decreased self-reported function and quality of life is evident. A major limitation is the focus on adolescent and young adult populations, leaving the impacts of CAI on general health and quality of life throughout the lifespan unknown.